Prolonged increase in digital blood flow following iloprost infusion in patients with systemic sclerosis. Issue 742 (August 1987) - Rademaker, M.; Thomas, R. H.; Provost, G.; Beacham, J. A.; Cooke, E. D.; Kirby, J. D.
Abstract : Thirteen patients with Raynaud's phenomenon secondary to systemic sclerosis received three 8-hour infusions of a synthetic prostacyclin analogue (Iloprost) on consecutive days and were followed-up over a period of 10 weeks during the winter of 1985/86. Six weeks after infusion, digital peripheral vascular resistance had fallen (P less than 0.05) and dicrotic notch proportion of pulse amplitude increased (P less than 0.05). Digital blood flow and pulse amplitude (measured by photoplethymography) were also increased but did not reach statistical significance. The trend of improvement in these blood flow parameters was still evident after 10 weeks. The number of cutaneous lesions (digital ulcers, etc) fell from 26 lesions before infusion to only 7 lesions by the end of the study, confirming the subjective improvement reported by the patients.